2005
DOI: 10.1111/j.1472-765x.2005.01735.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Bifidobacterium longum BB536 in medida (fermented cereal porridge) and their survival during refrigerated storage

Abstract: Aims: To develop medida, a Sudanese fermented thin porridge as a probiotic dietary adjunct with high total solids. Methods and Results: Fifteen per cent brown rice flour of 2-day-old malted paddy and skim milk were used for formulation. Levels of 2AE25, 4AE5 and 10% of added skim milk were studied. The initial pH was 6AE7 and fermentation was run to a final pH of 4AE4 using culture of Bifidobacterium longum BB 536. The highest count of 9AE9 ± 0AE07 log CFU ml )1 was obtained with 10% of added skim milk. The to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
3
12
0
2
Order By: Relevance
“…5, No. 2; porridge made of rice flour and skim milk, reaching a count of 9.9 log CFU/mL, and decreasing by 0.9 log CFU/mL during a two-week storage period (Kabeir et al, 2005). These studies, including our own, demonstrate that rice flour allows significant probiotic growth; however, it is difficult to compare due to various time frames and probiotic strains.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…5, No. 2; porridge made of rice flour and skim milk, reaching a count of 9.9 log CFU/mL, and decreasing by 0.9 log CFU/mL during a two-week storage period (Kabeir et al, 2005). These studies, including our own, demonstrate that rice flour allows significant probiotic growth; however, it is difficult to compare due to various time frames and probiotic strains.…”
Section: Discussionmentioning
confidence: 92%
“…Antioxidants in bran rice may act as a prebiotic that can help control colitis by managing microbial colonies in the digestive tract (Saman et al, 2009). Studies that have tested rice flour in fermented milk-based gruels, porridges, and puddings showed good growth and survival of various Lactobacillus strains such as L. rhamnosus GG (Espirito-Santo et al, 2014;Helland et al, 2004;Kabeir et al, 2005;Saman et al, 2009). …”
Section: Ricementioning
confidence: 99%
See 1 more Smart Citation
“…However, high counts of culture bacteria in fermented rice milk samples, the acidity percentages and rates of acidity development were low in these treatments comparing with those of fermented cow milk. That could be due to the high acids production and accumulation in cow milk samples or reduction of availability of nutrient required for the growth as stated by Kabeir et al, 38 …”
Section: Changes In Acidity Ph and Eh During Fermentation Of Cow Somentioning
confidence: 99%
“…Even though, the strain still at a level complying with the standard population requirement for probiotic product to benefit the host. In previous investigation Kabeir et al (2005) reported that survivability of B. longum BB536 under refrigeration storage of fermented Sudanese Medida beverage was not affected for a period of 2 week refrigeration storage. While Akalin et al (2004) noted a significant reduction on B.longum BB46 in yogurt after only one week refrigeration.…”
Section: Survival Of B Infantis During Refrigeration Storage Of the mentioning
confidence: 91%